Mental health symptoms and disorders in Paralympic athletes: a narrative review. Issue 12 (8th June 2019) - Swartz, Leslie; Hunt, Xanthe; Bantjes, Jason; Hainline, Brian; Reardon, Claudia L
Abstract : Objectives: This narrative review summarises the literature on the mental health of Paralympic athletes, explores possible reasons for the paucity of research in this area and suggests directions for future research. Methods: A systematic search of PubMed, PsycINFO, Cumulative Index to Nursing and Allied Health Literature, SPORTDiscus, Scopus, and Cochrane databases was conducted using search terms related to disability, sport and mental health. Results: The search yielded 665 publications. Of these, 129 were duplicates, resulting in 536 publications identified for initial screening. A total of 72 publications were to be relevant at initial screening. Only seven publications addressed Paralympic athletes specifically. Of these papers, three included measures of depression and three included measures of anxiety. In the studies that were not concerned with mental health symptoms or disorders, the focus of enquiry included identity and self, stress, and well-being. Conclusion: Most of the studies reviewed are small in scale, and there are almost no comparative data on Paralympic versus Olympic athletes. There is a paucity of data on rates of mental health symptoms and disorders in this population and the factors that might contribute to poor mental health among elite athletes with disabilities. We propose that stereotypes about people with disabilities—and the disability rights movement's rightful reaction to these stereotypes—have created barriers to mental health research among Paralympic athletes. There is a need for enquiry into the differential stressors experienced by Paralympic athletes, including trauma, transition out of sport, sport and personhood, and the potential for disability sport to promote psychological health.